2007
DOI: 10.1161/circulationaha.106.650671
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Induces Endothelial Dysfunction in Lepr db Mice

Abstract: Background-We hypothesized that the inflammatory cytokine tumor necrosis factor-␣ (TNF) produces endothelial dysfunction in type 2 diabetes. Methods and Results-In m Leprdb control mice, sodium nitroprusside and acetylcholine induced dose-dependent vasodilation, and dilation to acetylcholine was blocked by the NO synthase inhibitor N G -monomethyl-L-arginine. In type 2 diabetic (Lepr db ) mice, acetylcholine-or flow-induced dilation was blunted compared with m Lepr db , but sodium nitroprusside produced compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
221
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(243 citation statements)
references
References 24 publications
16
221
0
6
Order By: Relevance
“…After binding to the TNF-α receptor on the cell membrane of VECs, TNF-α exerts its biological effect via multiple pathways (11)(12)(13)(14)(15) to induce inflammation and alter coagulant/fibrinolytic function of VECs (16), leading to inflammation and coagulation. In the present study, a TNF-α-induced VEC injury model was established to investigate alterations in cell morphology and subcellular structures.…”
Section: Discussionmentioning
confidence: 99%
“…After binding to the TNF-α receptor on the cell membrane of VECs, TNF-α exerts its biological effect via multiple pathways (11)(12)(13)(14)(15) to induce inflammation and alter coagulant/fibrinolytic function of VECs (16), leading to inflammation and coagulation. In the present study, a TNF-α-induced VEC injury model was established to investigate alterations in cell morphology and subcellular structures.…”
Section: Discussionmentioning
confidence: 99%
“…36 Increases in TNF-a expression induce activation of NADPH oxidase and production of ROS. 37 Increased myocardial IL-6 expression is associated with the progression of heart failure. 38 IL-6 is produced by myocardium in heart disease and might be stimulated by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that tumor necrosis factor-α (TNF-α) is a major risk factor in atherosclerosis and coronary heart disease (8). TNF-α is a pleiotropic inflammatory cytokine that has been reported to serve a pathophysiological role in vascular atherosclerosis (9,10). In addition, TNF-α has been demonstrated to regulate the proliferation, apoptosis, migration and differentiation of VSMCs, which are critical in the pathogenesis of cardiovascular disease (8,11,12).…”
Section: Introductionmentioning
confidence: 99%